(untitled) (Journal of Scientific Research, 2017)
The nanocomposite particles named as ?-Al2O3/Fe3O4/SiO2/poly(glycidyl methacrylate) or ?-Al2O3/Fe3O4/SiO2/PGMA were prepared by multi-step process. At first, ?- Al2O3 nanoparticles were prepared by sol-gel method. Magnetite, Fe3O4, nanoparticles were then precipitated by in situ co-precipitation in presence of ?-Al2O3 particles, followed by incorporation of mesoporous silica layer using Stöber process. Finally, the surface of the ?-Al2O3/Fe3O4/SiO2 nanocomposite particles was modified by seeded polymerization of GMA using free radical polymerization. The surface modification, morphology and size distribution of the prepared nanocomposite particles were confirmed by FTIR, scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). The adsorption capacity of ?-Al2O3/Fe3O4/SiO2/PGMA nanocomposite particles was evaluated using remazol navy RGB (RN-RGB) as a model dye.